Treatment of corneal squamous cell carcinoma using topical 1% 5‐fluorouracil as monotherapy. (15th June 2015) - Dorbandt, Daniel M.; Driskell, Elizabeth A.; Hamor, Ralph E.
Abstract: The purpose of this report is to discuss the use of topical 1% 5‐fluorouracil as a sole therapy for canine corneal squamous cell carcinoma (SCC). A 12‐year‐old castrated male pug was evaluated for a well‐demarcated, central, 3 mm in diameter, pale pink, raised, right corneal mass. An incisional biopsy was obtained using a #64 beaver blade after topical anesthesia and without sedation. A definitive diagnosis of corneal SCC was obtained after histopathologic evaluation of the biopsy. Topical 1% 5‐fluorouracil ointment was applied to the right eye four times daily for 2 weeks followed by no treatment for 2 weeks, then treatment again twice daily for 2 weeks. The cornea remained free of recurrence 10 months after cessation of treatment. In dogs affected with corneal SCC, topical 1% 5‐fluorouracil monotherapy may be a viable and cost‐effective treatment option with minimal side effects. This chemotherapy agent may also have an effect on corneal pigmentation. Chronic cyclosporine therapy did not contribute to the pathogenesis of corneal SCC in the case described.